2023
DOI: 10.12912/27197050/163124
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Winter Wheat (T.Aestivum, T.Durum, T.Spelta) Depending on Varietal Characteristics in the Context of Climate Change

Abstract: This article presents the results of studies of winter wheat species and varieties depending on the meteorological conditions of the research years. The purpose of the research is to determine the density of the productive stem, the mass of 1000 grains, the yield and quality of winter wheat grain, depending on the species and varietal composition. Methods. Experimental studies were conducted during 2015/2016-2020/2021 yrs in the experimental field of Mykolaiv National Agrarian University (Ukraine). Agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In my own research, this was confirmed, but only at the optimal sowing date. Korkhova et al [54], on the other hand, have concluded that the quality of wheat grain is primarily influenced by weather conditions. Wojtkowiak et al [55] have argued that the nutritional and technological value of wheat is primarily influenced by genetic traits of varieties, environmental conditions, including weather and soil, as well as agronomic practices.…”
Section: Resultsmentioning
confidence: 99%
“…In my own research, this was confirmed, but only at the optimal sowing date. Korkhova et al [54], on the other hand, have concluded that the quality of wheat grain is primarily influenced by weather conditions. Wojtkowiak et al [55] have argued that the nutritional and technological value of wheat is primarily influenced by genetic traits of varieties, environmental conditions, including weather and soil, as well as agronomic practices.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the results of a study conducted during 2015-2017 in the Lublin Voivodeship (Poland), it was determined that winter wheat, regardless of the year of the study, generated the highest yield of soft winter wheat varieties -7.69 t/ha (Rachon et al, 2020). In addition, a higher yield (5.91 t/ha) was obtained by research in the period 2016-2022 on average for winter wheat varieties (Korkhova et al, 2023). N.V. Pinchuk et al (2022) determined that in the variants where pre-sowing inoculation of winter wheat seeds of the Skagen variety was conducted with biological products, the stem density was higher compared to the data obtained in the control variant.…”
Section: Source: Compiled By the Authorsmentioning
confidence: 96%
“…The main symptom of climate change is a drop in the level of moisture supply against a background of significant warming (Dudiak et al, 2019;Pichura et al, 2021Pichura et al, , 2022. Moisture has become a determining factor in all soil-climatic zones of Ukraine (Korkhova et al, 2023). Consequently, the problem of retaining soil moisture and increasing plant resistance to moisture deficit is topical.…”
Section: Introductionmentioning
confidence: 99%